THU0714 Investigating the effects of hypermobility on balance variables. (15th June 2017) - Selmani, M; Elvan, A; Akcay, B; Kenar, G; Birlik, AM; Angin, S; Simsek, IE
Abstract : Background: Hypermobility syndrome (HMS) is a clinical syndrome in which the range of motion of the joint is observed above normal ranges without being associated with a rheumatic disease. Excessive joint motion in HMS reduces joint stability and joint position sense and also can cause pain. Decreased muscle tone and tensile forces of the tendons cause decreased locomotor system stiffness and impairment of proprioception mechanisms. These problems in proprioceptive mechanisms can lead to balance-related disorders in individuals with hypermobility syndrome Objectives: The aim of this study was to investigate the possible effects of hypermobility on balance variables. Methods: 50 hypermobile (5 males and 45 females) volunteers diagnosed with Brighton Scale and 50 healthy (21 males and 29 females) volunteers were included in this cross sectional study. Participants with a score of 4 or over according to the Beighton scale were referred to a rheumatologist and were administered Brighton scale. Participants who were diagnosed by the physician were included in the hypermobile group. The objective balance evaluation was conducted using a balance platform. Evaluation variables were; static balance on single foot, static balance on both feet, limits of stability test and tandem walking. analysis was performed using independent samples t-test. Results: The mean age was found 21, 69±2, 13 years old for the control group and 20, 09±2, 65 years old for the HMS group. Body Mass Index was found 22, 13±3, 54 kg/m 2 in the control group and 21, 54±3, 50 kg/m 2 in the HMS group. HMS group showed significant wider step width in tandem walking (p=0, 001), significantly longer reaction time (p=0, 23, p=0.030), significantly higher end-point excursion (p=0.003, p=0, 026, p=0, 049), significant higher mean maximum excursions (p=0.018) (Table 1 ). Conclusions: In this study it was found that hypermobility has significant effects on the stability limits test and tandem walking. In previous studies it was found that hypermobility affects the static balance assessment variables (1, 2), but in this study dynamic balance assessment variables were affected. References: Iatridou K, Mandalidis D, Chronopoulos E, Vagenas G, Athanasopoulos S. Static and dynamic body balance following provocation of the visual and vestibular systems in females with and without joint hypermobility syndrome. J Bodyw Mov Ther. 2014 Apr;18(2):159–64. doi: 10.1016/j.jbmt.2013.10.003. Juul-Kristensen B, Johansen K, Hendriksen P, Melcher P, Sandfeld J, Jensen BR. Girls with generalized joint hypermobility display changed muscle activity and postural sway during static balance tasks. Scand J Rheumatol. 2015 Sep 1:1–9. Disclosure of Interest: None declared